Дослідження методів реалізації технології ІР-телефонії на сервері CISCO Unified Communications Manager - Сабурова, С. О.; Новіченко, Є. О. (ХНУРЕ, 2022)
More than ever, employees want greater mobility and workplace flexibility. They no longer want to commute to a workplace. Instead, they want to do their job from the comfort of their home with a suite of remote work tools that help keep them connected. For many enterprises, that means a larger use of unified communications – or the consolidation of existing communications tools into a single platform. This change is already underway: 34.3% of businesses have reduced IT spending by an average of $161k a year by eliminating redundant apps and shifting to cloud-based unified communications as a service (UCaaS) solutions. One of the key tools used to bolster unified communication for IP-telephone this is server Cisco Unified Communications Manager.
Keywords: ІР-телефонія; проблеми електромагнітної сумісності; конфігурація